2015
DOI: 10.1515/agri-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Microarray Expression Profiling Of Maize Roots Treated With Cadmium And Nickel

Abstract: Here, we report the effectiveness of antibody microarray expression profiling (AbMEP) procedure to determine similarities and differences between two maize cultivars (Premia and Blitz) exposed to various concentration of cadmium (Cd), nickel (Ni), as well as simultaneous exposure to both metals (Cd + Ni) for 0, 12 and 24 h. After protein extraction from control (untreated) and heavy metals (HM)-treated root pairs and their fluorescent labelling, the protein extracts were used for the AbMEP procedure and wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…To investigate how the transcription of these genes changes during phytohormone-induced PCD, two caspase-like protein genes, metacaspase type II (gene identifier 100285605) and putative metacaspase (gene identifier 100191541) (Ahmad et al, 2012), and three PCD inhibition genes, hexokinase (gene identifier 100192075), fdad1 (gene identifier 541686), and ABP9 (GenBank accession no. GU237073) (Zhang et al, 2011;Repka et al, 2015), were selected for analysis in this study. Quantitative real-time PCR analysis revealed that the expression of two metacaspase genes was increased at the late stage of GA-induced PCD, and the expression of three PCD inhibition genes increased initially, which then decreased at the stage of GA-induced PCD (Supplemental Fig.…”
Section: Ga Induces Pcd In the Maize Embryoless Aleurone Layersmentioning
confidence: 99%
“…To investigate how the transcription of these genes changes during phytohormone-induced PCD, two caspase-like protein genes, metacaspase type II (gene identifier 100285605) and putative metacaspase (gene identifier 100191541) (Ahmad et al, 2012), and three PCD inhibition genes, hexokinase (gene identifier 100192075), fdad1 (gene identifier 541686), and ABP9 (GenBank accession no. GU237073) (Zhang et al, 2011;Repka et al, 2015), were selected for analysis in this study. Quantitative real-time PCR analysis revealed that the expression of two metacaspase genes was increased at the late stage of GA-induced PCD, and the expression of three PCD inhibition genes increased initially, which then decreased at the stage of GA-induced PCD (Supplemental Fig.…”
Section: Ga Induces Pcd In the Maize Embryoless Aleurone Layersmentioning
confidence: 99%